Investigating the N-shaped EKC in China: An imperious role of energy use and health expenditures - Narcisse, Mulinga; Zhang, Shiyun; Shahid, Muhammad Sadiq; Shehzad, Khurram (Frontiers in Environmental Science, 2023)
Since the industrial revolution, the concentration of greenhouse gases (GHGs)has been increasing steadily. It is to be noted that China emitted 27% of the world’s GHGs in 2019, making it the world’s most significant contributor to climate degradation. The key objectives of this investigation are to ascertain the N-shaped association between CO2 emissions and economic growth in the presence of energy use and domestic government health expenditures. In addition, the research inspected the role of Belt and Road Initiative through economic globalization in China. This study utilized the autoregressive distributed lag model and found that an N-shaped environmental Kuznets curve exists in China. Furthermore, the study discovered that economic globalization improves ecological excellence in the short run. Nonetheless, energy consumption and health expenditures considerably amplify the intensity of CO2 emanation in China in the long run. The research suggested that installing green industries through economic globalization can imperatively lessen environmental degradation. Moreover, installing technological firms will be more beneficial in the long run to overcome environmental degradation rather than importing from other countries. The study elaborated momentous causation effects among the study variables through the Granger causality test.